An industrial quality control study on Columbia Wire & Cable Corporation - Caw, Eunice; Lapid, Norman; Lim, Loubert Peter (Diliman, Quezon City College of Engineering, 2003)
This study analyzes the production and quality systems of Columbia Wire and Cable Corporation specifically its Heat-Resistant Thermoplastic wires with Nylon (THHN) wires line. The main concern of this study is further lowering the rate of rejection in the production of THHN wire. The company suffered more rejects in the production of THHN wires as compared with their other product lines, from the month of January to June 2002, around two hundred forty three kilometers (243 km) of THHN wires did not pass their quality tests because of factors such as wrong elongation, concentricity and porosity. These products were either sold with customer concession or considered as waste. The study focuses on how it can help the company improve thew wire and cable production process, material yield and process capability through statistical process control, process capability analysis, acceptance sampling and quality management tools. Analysis is only limited on the final tests conducted by the company on their finished products. Having decided to focus THHN wire, Pareto analysis was performed on the data regarding nonconforming THHN wire in order to pinpoint the quality characteristics which are the source of the THHN wire rejections. Concentricity, Porosity, and Elongation result in greater quantities of wire rejected compared to the other quality characteristics. Therefore, these three quality characteristics were chosen as the focus of the group's study in Industrial Quality Control. These findings are reflected in the Failure Mode, Effect and Criticality Analysis. Individual and Moving Range Chart (x and Rm) was used in testing the data for elongation and concentricity characteristics of the THHN wires. The X and Rm chart is used because the production is a batch process and small number of data is available. Since sample size n = 1, the Shewhart control chart for individual measurements and the moving range was made. The level of variation of concentricity is within tolerable limits, however, out-of-control points occurred during the month of May. Closer inspection and the application of tests for assignable causes revealed that there were incorrect or off-center loading of conductor on may 16th and PVC exposed to moisture on May 31st. Nine consecutive points were reported above the center line on June 21. Despite the group's efforts to identify the reason behind this, the cause of the pattern is unknown. Similar to the analysis performed on the data for concentricity, Shewhart control charts for individual measurements and the moving range was made based on percent elongation on the Final Inspection results obtained from tests performed on one sample from each batch of wire produced. There are a total of nine separate points which fell above the upper control limit for moving ranges. From the chart made one can tell that the company should look into fine-tuning their processes so that variation in percent elongation will be minimized. Examination of the control charts revealed that there are points outside the control limits spread throughout three months, on April 3, April 20, May 22, and June 10. The reason behind this is the same as the root cause for the moving ranges to be out of control; that is, the lack of a proper setting for the gasoline output to regulate the conductor temperature as it is being coated with insulating material. By applying the tests for special causes, the group concluded that the production process is out of control for percent elongation of wire. Process capability potential Cp, and process capability index Cpk are of equal value of 0.4702. The value for Cp and Cpk for concentricity are much lower than the recommended minimum value of 1.25. s much as 7.93% of all units produced are nonconforming due to low concentricity. Therefore, corrective action must be undertaken to improve process capability immediately. The group recommends marking the loading mechanism to ensure the wire is centered as it goes through the extrusion process. The maintenance procedure for dies should also be reviewed, to see if concentricity can be improved by preventing the use of rough or misaligned dies. Similar to the Process Capability Analysis on Cencentricity, the results of the analysis for the percentage elongation suggest that the process is not capable of meeting specification limits since Cp and Cpk are only equal to 0.8252. This means that 0.66% of the units produced will have insufficient percentage elongation to meet specification limits.
The np chart is used to analyze the data for porosity where "np" is the number of nonconforming items in the sample. From the np chart, it can be said that porosity occurs rarely enough such that even one instance of detecting is enough for the data to go out of control. Porosity was detected in 7 out of these 8 batches, where all occurred on May 31, when out-of-control points for concentricity occurred as well. Clearly, a special cause exists which resulted in the poor values of the quality characteristics of the wire produced on this date. This was identified to be moisture contaminating the PVC supplies during storage. For June 10, the batch with porosity was the same as the batch which had a measurement for percent elongation which fell below the lower control limit. It was concluded that they share the same assignable cause - the failure of the production operator to properly regulate the temperature of the PVC. For June 11, the most likely cause of the porosity was the malfunction in the machine, such as a damaged blower or thermocouple, which affected its temperature. One root cause of insufficient concentricity is that operators have to estimate when they load the wire for extrusion whether or not it's in the center as it goes through the machine which adds the PVC insulation. Since the loading mechanism is simply composed of four adjustable bolts, the group recommends putting markers on the bolts so that operators know when they have loaded the wire properly such that it will pass through the exact center of the dies. It is necessary to conduct heat treatment on the copper wire to prepare it for being coated with PVC insulation prior to extrusion. However, production operators do not know exactly what gasoline output setting is appropriate so the copper can be heated properly. Sometimes, workers set the gasoline input too low, reportedly to save gasoline. Different operators using different gasoline output settings also is one root cause of high variation in the percentage elongation, and sometimes causes porosity as well, if the setting is too high. Regression analysis should be performed to estimate an equation for the percentage elongation as a function of the gasoline output and the ambient temperature. Once the regression analysis is conducted, the company can tabulate proper values for the gasoline output settings for different atmospheric temperatures. They can then mark the knobs which control gasoline output accordingly. One problem which occurred during the study period was a case of some PVC supplies being ruined upon exposure to excessive moisture in the air. The company considers instances of porosity a serious problem in their production process, and the resulting poor quality of the PVC from its exposure to moisture led to 221,850 kilometers of wire produced on may 31 being rejected by the company. To prevent this occurring again, the group recommends buying and installing a dehumidifier and hydrothermometer in the storage section of their production plant. Columbia Wire and Cable Corporation frequently inspect for the quality of their product throughout all stages of production, but they don't analyze nor interpret long term performance, or even measure the variability in their process. Only rejects and nonconformities signal their Quality Control Division when something has gone wrong, when in fact there are methods which exist, such as control charts used, which allow them to detect problems in their process even before nonconforming units are actually produced and tested. Therefore, the group recommends the implementation of Statistical Process Control, or SPC, a collection of tools and techniques which help to detect problems and subsequently find solutions to them. Other areas that require further study is the implementation of Total Productive Maintenance, or TPM. The group recommends reviewing the possibility of improving their maintenance process in order to prevent machine malfunctions and breakdowns from adversely affecting the process quality characteristics of porosity, concentricity, and percentage elongation.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Columbia Wire and Cable Corporation; Wire industry; Quality control